Successful Implementation of an Automated Sedation Vacation Process in Intensive Care Units. (September 2016) - Ackrivo, Jason; Horbowicz, Kevin J.; Mordino, Jason; El Kherba, Maryam; Ellingwood, Jennifer; Sloan, Karin; Murphy, Jaime
This quality improvement initiative sought to develop a sedation vacation (SV) protocol to increase SV performance and ensure sustainability. A standardized, nurse-driven SV protocol within the electronic medical record was implemented in adult intensive care units (ICUs) at Boston Medical Center. For 6 months, data were collected on the number of assessments performed, SV completion, SV eligibility, and reason for exclusion. Secondary outcomes included ICU length of stay (LOS) and ventilator LOS. Of 1730 patient-days during this 6-month period, SV assessments were performed 70% (n = 1211) of the time. SVs were conducted on 60.0% (n = 726) during days in which an assessment occurred. There was no significant change in ICU LOS or ventilator LOS during the study period. This SV protocol attained a 70% adherence rate, which was sustained over the 6-month period. There were no significant changes in secondary outcomes.